INFECTIOUS CAUSES OF PRURITUS OF PREGNANCY: A STUDY ON EVALUATION AND OUTCOME - Beant Singh; Parneet Kaur; Dimple Chopra; Mandeep Kaur; Sameeksha Verma (GMC Patiala Journal of Research and Medical Education, 2024)
Introduction: Pruritus in pregnancy is a common and burdensome symptom that can occur due to various underlying conditions. It may be the first sign of a pregnancy-specific pruritic disease or a dermatosis that coincides with pregnancy by chance. It is essential to recognize and address this symptom promptly, as some conditions can have detrimental outcomes for both the mother and the foetus. Aims & Objective: To analyse the various infectious causes of pruritus in pregnancy and their maternal and foetal outcomes. Material & Method: The present study was conducted in Department of Obstetrics & Gynaecology and Department of Venerology & Dermatology, GMC & Rajendra Hospital, Patiala. It was an observational prospective study in which all the cases presenting with pruritus were taken during the period from May 2020 to April 2021. Results: During the study period, 218 pregnant women presented with complaint of pruritus. Infection was the most common cause of pruritus in pregnancy accounting for 46.3% subjects. The most commonly reported infection was fungal infection (17.4%). Vaginitis accounted for 15.1% cases with candida vaginalis being the most common (7.8%). Maternal and fetal complications were Preterm delivery, Premature rupture of membrane (PROM), preterm premature rupture of membrane (PPROM), Premature babies and NICU admission. Conclusion: This study highlights the various causes of pruritus in pregnancy. Infection contributes the major cause of pruritus in pregnancy followed by specific dermatoses in pregnancy. In mother pruritus can cause sleep disturbance and affect quality of life. Among infectious causes like candida vaginalis, bacterial vaginosis and trichomonas can cause preterm delivery, PROM, PPROM, oligohydramnios and LBW babies. Chicken pox in early trimester can cause congenital varicella syndrome. Thus, early diagnosis and prompt treatment can improve maternal and fetal prognosis and can decrease morbidity.